A case series on necrotising fasciitis of breast: a rare but debilitating disease - Gayathre, S. P.; M., Kudiyarasu; S., Bala Brindha; Kannan, R. (International Surgery Journal, 2021)
Necrotising fasciitis of breast being a rare disease has only a meagre number of cases being reported and most commonly seen following trauma or surgical procedure to the breast. The reported cases have shown a predilection for lactating mothers with a history of surgical intervention to breast. This case series included 3 cases of necrotising fasciitis with varied etiologies in various age groups including a lactating mother, an immunocompromised patient and another patient with no other risk factor such as trauma or surgical intervention to breast and the subsequent difference in extent of surgical intervention and management in these patients. Extensive surgical debridement at the earliest was the mainstay of treatment in all three cases.